1978
DOI: 10.2307/2273517
|View full text |Cite
|
Sign up to set email alerts
|

On the compactness of ℵ1 and ℵ2

Abstract: In recent years, the Axiom of Determinateness (AD) has yielded numerous results concerning the size and properties of the first ω-many uncountable cardinals. Briefly, these results began with Solovay's discovery that ℵ1 and ℵ2 are measurable [8], [3], continued with theorems of Solovay, Martin, and Kunen concerning infinite-exponent partition relations [6], [3], Martin's proof that ℵn has confinality ℵ2 for 1 < n < ω, and very recently, Kleinberg's proof that the ℵn are Jonsson cardinals [4].This paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…An argument similar in spirit to that of 2.1.12 answers a question of [1]. Namely, assuming ZF + ADR + 0 is regular, one can show that the two supercompactness measures on Pw(co2) defined in [1] are both identical to the measure defined (implicitly) in [8, §3].…”
Section: Proof Suppose P Lh Vx G R 3 Vmentioning
confidence: 91%
“…An argument similar in spirit to that of 2.1.12 answers a question of [1]. Namely, assuming ZF + ADR + 0 is regular, one can show that the two supercompactness measures on Pw(co2) defined in [1] are both identical to the measure defined (implicitly) in [8, §3].…”
Section: Proof Suppose P Lh Vx G R 3 Vmentioning
confidence: 91%
“…Since any cardinal γ which is δ +α supercompact is automatically <δ supercompact, by the remarks immediately following the proof of Lemma 2.1, we know that in V P , δ is a limit of cardinals γ which are <δ supercompact. As V P "δ is δ +α strongly compact", by a theorem of DiPrisco [7], V P "Any cardinal γ which is either <δ supercompact or <δ strongly compact is δ +α strongly compact". Thus, in V P , δ is a limit of cardinals γ which are δ +α strongly compact, a contradiction.…”
Section: Proofmentioning
confidence: 99%
“…On the other hand, Solovay showed that if U is a K-complete, normal ultrafilter over PKA, and {/a's over PKa for k < a < A are defined by A E Ua if and only if {y G PKA: y D a E A} E U, then the glued-together ultrafilter over PKA of the Ua's does not have the partition property (see [2]). …”
Section: Claim {X E a : F(x(t])) G X For Every Tj < K} G û Proof Ofmentioning
confidence: 99%
“…These ultrafilters in turn can be "glued together" with a measure on X to again produce an ultrafilter over PKX. In general, the ultrafilter over PKX obtained by this method is not the same one which is started out with (see [2]). In §3 it is shown that if the ultrafilter constructed over PKX in §2 is restricted to ultrafilters over PKa for k < a < X, then glued together with the measure constructed on X in this same section, the glued together ultrafilter is the same as the one started out with.…”
mentioning
confidence: 99%
See 1 more Smart Citation